Molecular programs of fibrotic change in aging human lung - Seoyeon Lee (Nature Portfolio, 2021)
Age is associated with increasing vulnerability to both acute and chronic lung diseases. Employing genomic analysis and live lung imaging, this study reveals a profile of increased cellular senescence, telomere shortening, and fibrosis-induced impaired alveolar function in the natural history of human lung aging.